Firework displays, firework dramas and illuminations - precursors of cinema? - Watanabe-O'Kelly, H (Blackwell Publishers Ltd., 1995)
However one defines cinema, its ability to create a moving image by means of light and colour, its capacity for dramatic presentation and the typical experience of the audience in which a large number of people congregate in the dark and look up at a magnified image glowing in front of and above them must emerge as important characteristics. Since all these features are to be found in the firework display in the sixteenth and seventeenth centuries, they have as much claim to be cited as forerunners of cinema as the mechanical devices of the early nineteenth century more frequently mentioned. This contention is illustrated in what follows by means of German examples.